2021
DOI: 10.1002/ange.202110116
|View full text |Cite
|
Sign up to set email alerts
|

Cation‐Exchange‐Induced Metal and Alloy Dual‐Exsolution in Perovskite Ferrite Oxides Boosting the Performance of Li‐O2 Battery

Abstract: Atemperature-controlled cation-exchange approach is introduced to achieve aunique dual-exsolution in perovskite La 0.8 Fe 0.9 Co 0.1 O 3Àd where both CoFea lloy and Co metal are simultaneously exsolved from the parent perovskite,f orming an alloya nd metal co-decorated perovskite oxide.M ossbauer spectra showt hat cation exchange of Fe atoms in CoFea lloy and Co cations in the perovskite is the key to the co-existence of Co metal and CoFealloy. The obtained composite exhibits an enhanced catalytic activity as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The obtained composites demonstrated an excellent specific discharge capacity of 6549.7 mA h g À1 and a cycle stability of 215 cycles when used in Li-O 2 batteries. 135 In the structure of perovskite oxides, doping at the A-site may form O defects, which indirectly affects the ORR/OER activity of perovskite oxides. The doping of different ions in the B-site directly can influence the B-O-B angle, thereby increasing the intrinsic activity.…”
Section: Lithium-air Batterymentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained composites demonstrated an excellent specific discharge capacity of 6549.7 mA h g À1 and a cycle stability of 215 cycles when used in Li-O 2 batteries. 135 In the structure of perovskite oxides, doping at the A-site may form O defects, which indirectly affects the ORR/OER activity of perovskite oxides. The doping of different ions in the B-site directly can influence the B-O-B angle, thereby increasing the intrinsic activity.…”
Section: Lithium-air Batterymentioning
confidence: 99%
“…The obtained composites demonstrated an excellent specific discharge capacity of 6549.7 mA h g −1 and a cycle stability of 215 cycles when used in Li–O 2 batteries. 135…”
Section: All-inorganic Perovskite For Other Energy Storage Batteriesmentioning
confidence: 99%
“…The CoFe alloy catalyst synergistically improved the OER and ORR characteristics of Li−O 2 batteries compared with single-metal Co or Fe exsolution systems. Cong et al 128 reported the enhanced catalytic performance of CoFe alloy nanoparticles on a La 0.8 Fe 0.9 Co 0.1 O 3−δ perovskite scaffold. The CoFe alloy exsolution electrode exhibited a low overpotential and remarkable redox stability over more than 200 cycles.…”
Section: Metal−air Batteriesmentioning
confidence: 99%
“…4,5 One of the most effective strategies to address these issues is to develop inexpensive and efficient cathode catalysts. 6,7 With the progress of research, cathode catalysts have become an important part of LOBs, among which carbon materials, 8,9 noble metals, 10,11 and non-noble metal compounds [12][13][14][15] have been widely studied to improve the performance of batteries.…”
Section: Introductionmentioning
confidence: 99%